Non-operative management of perforated diverticulitis with extraluminal or free air – a retrospective single center cohort study. (2nd November 2018) - Thorisson, A.; Nikberg, M.; Andreasson, K.; Smedh, K.; Chabok, A.
Abstract: Objectives: The aim of this study was to describe patient characteristics and results of non-operative management for patients presenting with computed tomography (CT) verified perforated diverticulitis with extraluminal or free air. Methods: All patients treated for diverticulitis (ICD-10: K-57) during 2010–2014 were identified and medical records were reviewed. Re-evaluations of CT examinations for all patients with complicated disease according to medical records were performed. All patients diagnosed with perforated diverticulitis and extraluminal or free air on re-evaluation were included and characteristics of patients having immediate surgery and those whom non-operative management was attempted are described. Results: Of 141 patients with perforated diverticulitis according to medical records, 136 were confirmed on CT re-evaluation. Emergency surgical intervention within 24 h of admission was performed in 29 (21%) patients. Non-operative management with iv antibiotics was attempted for 107 patients and was successful in 101 (94%). The 30-day mortality rate was 2%. The presence of a simultaneous abscess was higher for patients with failure of non-operative management compared with those that were successfully managed non-operatively (67% compared to 17%, p = .013). Eleven out of thirty-two patients (34%) with free air were successfully managed conservatively. Patients that were operated within 24 h from admission were more commonly on immunosuppressive therapy, had more commonly free intraperitoneal air and free fluid in the peritoneal cavity. Conclusions: Non-operative management is successful in the majority of patients with CT-verified perforated diverticulitis with extraluminal air, and also in one-third of those with free air in the peritoneal cavity.